Validity and reliability of a sport participant psychosocial well-being instrument: a preliminary study - Endang Sepdanius; Nurul Diyana Binti Sanuddin; Mohad Anizu Bin Mohd Nor; M. Adli Bin Mohd Sidi; Bekir Erhan Orhan; Mohd Salleh Aman; Rini Afriani (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose: This study aims to evaluate the validity and reliability of an instrument designed to measure the psychosocial well-being of sports participants.